Bending strength of timber beams rehabilitated with reinforced epoxy mortar plates - Duarte, A. (2011)
The need for restoration of the built heritage increases the demand for new strengthening and rehabilitation techniques of structures. This paper discusses a rehabilitation system for timber beams, consisting of the replacement of the decayed parts by new ones of nearly the same material, connected to the sound parts by reinforced epoxy mortar plates. The use of this technique allows for lighter and less intrusive works, compatible with the normal building occupation during the rehabilitation process. The experimental analysis undertaken focused on the flexural bonding behavior with stainless steel, reinforcement steel, and glass fiber reinforced plastic bars being used as alternatives. A simple analytical model, based on the usual assumptions of the bending theory, is proposed, leading to a reasonable agreement with the experimental results. In spite of a reduction of strength when compared to the original elements, the safety level of the rehabilitated elements is high enough to comply with the Eurocode 5 requirements and is, therefore, suitable for actual works.